No observable influence of COVID-19 inactivated vaccines on pregnancy and birth outcomes in the first trimester of gestation - Ting Du; Qiuxia Qu; Yawen Zhang; Qin Huang (Taylor & Francis Group, 2023)
Background While studies have demonstrated that certain COVID-19 vaccines administered during pregnancy did not affect neonatal or maternal outcomes significantly, the safety of inactivated SARS-CoV-2 vaccines in China, given during the first trimester, remains to be fully elucidated. Method A retrospective cohort study was conducted involving female participants who gave birth from January to October 2021. The study compared pregnancy, delivery, and neonatal outcomes between subjects who received one or two doses of the inactivated COVID-19 vaccines during their first trimester and unvaccinated control subjects. Results A total of 2658 pregnant women was recruited. Among them, 2358 (88.7%) reported ongoing pregnancies; 326 (13.8%) of these were vaccinated. Additionally, 277 (10.4%) experienced spontaneous miscarriages between 6 to 20 gestational weeks; 40 (14.4%) of these were vaccinated, yielding an odds ratio of 0.67-1.36 (95% confidence interval) for COVID-19 vaccination. The comparison of neonatal complications, including an Apgar score less than 7, preterm birth, low birth weight, and newborn respiratory complications, between unvaccinated and vaccinated participants revealed no statistical significance. Conclusion The administration of COVID-19 inactivated vaccines during the first trimester of pregnancy is not associated with adverse pregnancy or neonatal outcomes, providing a substantial ground for pertinent health education.